Living alone following first-ever stroke: A prospective study in Turkey identifying the risk factors and evaluating their effects - (:unkn) unknown (My University, 2007)
Introduction: The incidence of stroke, death, and dependency rates shows variability between countries and ethnic groups. The cost of management of stroke is extremely high. Thus, determination of controllable risk factors is important. The aim of this study was to evaluate the risk factors and the effects of risk factors on death rates, dependency, and stroke recurrence in hospitalised patients having first-ever stroke. Method: A total of 100 patients admitting to our hospital during the petiod April 2002 to March 2003 inclusive who were diagnosed as stroke according to WHO criteria were included in this study and evaluated prospectively. Results: The mean age of the patients was 66.7 ± 9.9 years and 60% was male. 76 of the patients had ischaemic stroke; 24 had hemorrhagic stroke. The death rates were 12% in the first 28 days and 26% in 6 months. The best predictors of death rate in 6 months were stroke severity, living alone, and prestroke dementia. Stroke severity was also the best predictor for dependency. Peripheral atherosclerosis, pre-stroke dementia, and stroke severity were the best predictors for recurrent stroke. Conclusion: Living alone may be an important predictive factor for survival, although its importance has been underestimated. © NZMA.